Muslims in Motion : Islam and National Identity in the Bangladeshi Diaspora. - Kibria, Nazli (Book collections on Project MUSE., 2011)
Muslims in Motion provides a comparative look at Bangladeshi Muslims in different global contexts-including Britain, the U.S., the Middle East, and Malaysia. Nazli Kibria examines international migrant flows from Bangladesh, and considers how such migrations continue to shape Islamization in these areas. Having conducted more than 200 in-depth interviews, she explores how, in societies as different as these, migrant Muslims, in their everyday lives, strive to achieve economic gains, sustain community and family life, and realize a sense of dignity and honor.